How efficient are specialized public health services in China? A data envelopment analysis and geographically weighted regression approach - Bai, Qian; Huang, Lieyu; Guo, Yan; Xu, Xin; Zhang, Zhouyixin; Wang, Yuan; Chen, Hao; Bian, Ying (Frontiers in Public Health, 2025)
BackgroundThe Chinese public health system is grappling with escalating demands, which stemmed from the challenges of preventing chronic and infectious diseases, as well as the aging population. Meanwhile, in the context of restricted public health resources, how to efficiently utilize these resources becomes a paramount concern.ObjectiveThis study aimed to evaluate the technical efficiency of specialized public health facilities, the major providers of public health services in China, then discuss its temporal and spatial distribution characteristics and finally investigate its influencing factors.MethodsThe super slacks-based measure data envelopment model was constructed to calculate the efficiency of specialized public health facilities of 31 provinces from 2017 to 2019. Stepwise regression was applied to sort out significant independent variables. Then, geographically weighted regression was used to analyze the spatially varying associations between efficiency and independent variables.ResultsOn average, the average technical, pure technical and scale efficiencies were 0.6569, 0.7336 and 0.9206, respectively. Notably, a subtle downward trend was observed in the technical efficiency, which declined from 0.6889 in 2017 to 0.6238 in 2019. From the efficiency decomposition, this reduction was mainly caused by the decreasing of scale efficiency. Besides, substantial geographic variations were observed, with the eastern region exhibiting greater levels of technical and pure technical efficiency. Contrarily, the western region appeared to perform better in terms of scale efficiency. Based on the geographically weighted regression, the proportion of public health expenditure had a noticeable negative impact on the technical efficiency, especially in partial central and eastern coastal provinces. On the other side, the ratio of older population, the sex ratio and the Nitrogen Oxides emission volume had positive impacts on technical efficiency with variations in coefficient magnitude across different geographic areas.ConclusionThe efficiency of specialized public health facilities has not achieved the optimal status, particularly in terms of the pure technical efficiency. Moreover, the geographic variation was a significant issue affecting the sustainable and balanced performance of public health delivery system in China. The spatially heterogeneous associations between macro-regional factors and efficiency provide in-depth insights in assisting local governments to formulate more targeted and effective interventions, thereby contributing to reduce regional disparities.